The uncertain self: Intolerance of uncertainty moderates the association of both positive and disorganized schizotypal traits with self-concept clarity in a non-clinical sample - Alexandra Kaszás; Szabolcs Kéri; Dorottya Bencze; Ágnes Szőllősi; Ágota Vass; Mihály Racsmány; Bertalan Polner (PLoS ONE, 2026)
Our objective was to investigate the relationship between self-concept clarity, intolerance of uncertainty, and schizotypal traits, with a focus on whether intolerance of uncertainty moderates the association between self-concept clarity and positive schizotypy in a non-clinical context. A sample of 315 adults (on average 43 (SD = 12) years, 247 women) completed the Self-Concept Clarity Scale, the Intolerance of Uncertainty scale, and the Schizotypal Personality Questionnaire – Brief Revised. Lower self-concept clarity was significantly associated with higher levels of positive, negative, and disorganized schizotypy, as well as with greater inhibitory intolerance of uncertainty. Importantly, a moderation analysis revealed that intolerance of uncertainty significantly altered the strength of the negative relationship between self-concept clarity and both positive and disorganized schizotypy. Specifically, this association was strongest among individuals with low levels of intolerance of uncertainty. In contrast, at higher levels of intolerance of uncertainty, the negative relationship between self-concept clarity and both positive and disorganized schizotypy was weaker. This pattern suggests that, among individuals with lower tolerance for uncertainty, a better-defined self-concept is more strongly associated with lower levels of positive and disorganized schizotypy. These results underscore the importance of considering both self-structure and uncertainty tolerance in models of schizotypy and psychosis risk. Our findings suggest that self-concept clarity and intolerance of uncertainty are interrelated cognitive factors that synergistically explain variance in schizotypal traits. As intolerance of uncertainty is a potentially modifiable cognitive process, the results have implications for early interventions aimed at reducing psychosis risk by improving self-concept clarity and tolerance for uncertainty. Although the study used a non-clinical sample, it supports a dimensional approach to psychosis and highlights key targets for future research.